Opioid Maintenance Therapy (OMT) Outcomes on Maternal Weight Gain [24E]. (May 2020) - Davis, Jay; Heiselman, Cassandra; Staszewski, Cara; Cochrane, Elizabeth; Gruttadauria, Michelle; Garretto, Diana
Abstract : INTRODUCTION: The Institute of Medicine's (IOM) guidelines provide recommendations for appropriate gestational weight gain based solely on pre-pregnancy body mass index (BMI). Opioid use disorders (OUD) are known risk factors for poor nutrition and inadequate weight gain. We sought to compare methadone vs buprenorphine OMT effects on obtaining appropriate maternal weight gain. METHODS: We conducted an IRB approved retrospective cohort study using electronic medical records from an academic center between 2007 and 2017. Inclusion criteria: women with a singleton pregnancy receiving OMT with either methadone or buprenorphine. Exclusion criteria: women with a pre-viable delivery, multiple gestation pregnancy, or anomalous fetus incompatible with life. We compared both OMT groups for differences in insufficient, appropriate, or excessive weight gain based upon IOM's guidelines. P -value <.05 was considered significant. RESULTS: 181 pregnancies were analyzed. 51% (n=93) received buprenorphine and 49% (n=88) received methadone. Patients in the methadone arm were more likely to be prescribed medications at a methadone/pain clinic vs OB provider ( P <.05). Baseline demographics for both groups were similar in age, parity, race and BMI. There were no statistically significant differences in inadequate, appropriate, or excessive weight gain between the 2 groups ( P =.47). Additionally, there were no statistical differences between the groups regarding recommended weight gain, regardless of BMI ( P =.53). CONCLUSION: The findings amongst our cohorts revealed there is no superiority of either OMT selection to achieve the recommended weight gain in pregnancy. This data illustrates that the decision to select the optimal OMT should be guided by other factors than achieving the ideal weight gain.